16th IHIW: Global analysis of registry HLA haplotypes from 20 Million individuals: Report from the IHIW Registry Diversity Group. (26th December 2012) - Maiers, M.; Gragert, L.; Madbouly, A.; Steiner, D.; Marsh, S. G. E.; Gourraud, P.‐A.; Oudshoorn, M.; van der, H.; Schmidt, A. H.; Pingel, J.; Hofmann, J.; Müller, C.; et al.
Summary This project has the goal to validate bioinformatics methods and tools for HLA haplotype frequency analysis specifically addressing unique issues of haematopoietic stem cell registry data sets. In addition to generating new methods and tools for the analysis of registry data sets, the intent is to produce a comprehensive analysis of HLA data from 20 million donors from the Bone Marrow Donors Worldwide (BMDW) database. This report summarizes the activity on this project as of the 16IHIW meeting in Liverpool.